Pengaruh Intellectual Capital terhadap Nilai Perusahaan melalui Profitabilitas sebagai Variabel Intervening - Hidayah, Nur; Patmasari, Eka Kurnia; Prasetyo, Ageng (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the effect of intellectual capital on firm value with profitability as an intervening variable in state-owned banking companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The development of globalization and a knowledge-based economy requires companies to rely not only on physical assets but also on intellectual assets, including knowledge, innovation, and the quality of human resources. This study employs a quantitative approach with a causal associative research design. The research sample consists of five state-owned banks, namely Bank Negara Indonesia (BNI), Bank Rakyat Indonesia (BRI), Bank Mandiri, Bank Tabungan Negara (BTN), and Bank Syariah Indonesia (BSI). The data analysis technique used is multiple linear regression based on Partial Least Square (PLS). The results indicate that intellectual capital has a significant effect on firm value but does not have a significant effect on profitability. Profitability, measured using Return on Assets (ROA), is proven to have a positive and significant effect on firm value. Furthermore, profitability does not significantly mediate the relationship between intellectual capital and firm value. These findings indicate that optimal management of intellectual capital can enhance firm value, although it does not directly lead to an increase in profitability.